IRSp53 controls plasma membrane shape and polarized transport at the nascent lumen in epithelial tubules - Sara Bisi (Nature Portfolio, 2020)
The I-BAR protein IRSp53 senses membrane curvature but its physiological role is unclear. Here, the authors show that during early lumen morphogenesis, IRSp53 controls the shape of the apical plasma membrane and polarized trafficking and ensures the correct epithelial tubular architecture and if deleted, affects renal tubules morphogenesis in various organisms.